1999
DOI: 10.4141/p97-144
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with the utilization of wastes in nursery potting mixes and as field soil amendments

Abstract: The nursery/landscape industry has been one of the fastest growing agricultural sectors in Canada. Since 1980s, the Ornamental Nursery Research Program at the Horticultural Research Institute of Ontario (HRIO) has been conducting research which focuses on environmentally friendly production practices. Emphasis is on the use of composted or uncomposted organic wastes as amendments in container potting mixes. Various projects have evaluated mixes derived from wastes such as spent mushroom compost, paper mill slu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…While nursery producers typically use less than one-third of wastes or composts in substrates (Chong 1999;Bugbee 2002), the results of this study indicate that greater volumes of these materials can be used, especially the composts from municipal waste and the Bio Soil paper sludge. For nursery container culture, we recommended previously that any amount of composted paper mill sludge could be used (Chong and Cline 1994) and up to 60% of raw paper mill sludge, depending on the source (Chong 2003).…”
Section: Discussionmentioning
confidence: 95%
“…While nursery producers typically use less than one-third of wastes or composts in substrates (Chong 1999;Bugbee 2002), the results of this study indicate that greater volumes of these materials can be used, especially the composts from municipal waste and the Bio Soil paper sludge. For nursery container culture, we recommended previously that any amount of composted paper mill sludge could be used (Chong and Cline 1994) and up to 60% of raw paper mill sludge, depending on the source (Chong 2003).…”
Section: Discussionmentioning
confidence: 95%
“…Any use of organic wastes in horticulture must consider potential hazards to the environment as well as benefits such as cost savings (Chong 1999). Contrary to common misconception, the paper mill sludges produced in Ontario, including the source used in this study, are relatively free of undesirable organic chemicals such as PCBs (polychlorinated biphenyls) or dioxins and are low in content of heavy metals (Chong 1999).…”
Section: Substrate Analysismentioning
confidence: 96%
“…At the Horticultural Research Institute of Ontario, we observed that growth of pot-in-pot shade trees decreased as the amount of soil increased from 10 to 100% by volume in substrates with or without peat plus bark (Murray et al 1997). We also demonstrated that many non-traditional, organic waste materials, such as spent mushroom substrate, recycled municipal waste, wood chips, and paper mill sludge can be used successfully as alternative and inexpensive amendments for growing shrubs in smaller 6-L (#2) containers (Chong 1999). Similar research has not been conducted with shade trees in large containers.…”
mentioning
confidence: 86%
“…(Vetter et al 2007) There are further options to use recycled wood chips and fibres as material. Applications encompass mulching material for soil covering and peat substitute for horticulture substrates (Chong 1999; see Chapter 24 of this book), structure material for sewage sludge composting (Lin et al 2001), beddings e.g. in riding schools and in breeding of various animals (Hester et al 1997, Anonymous 2000, Asari et al 2004, Burn & Mason 2005, production of low grade paper (Roffael & Dix 1993), mushroom production ; Fig.…”
Section: Other Types Of Materials Recyclingmentioning
confidence: 99%